Development of an Educational RPG Genre Game for Greedy Algorithm Material in 11th Grade Informatics Students - Ni'mah, Ana Tsalitsatun; Toyybah, Khafidotun; Sari, Ariesta Kartika; Fahmi, Muhammad Naufal; Arif, Muchamad; Ramansyah, Wanda (EDUTIC, 2025)
This research is motivated by the difficulties of grade XI students of SMA Negeri 1 Bangkalan in understanding the greedy algorithm material in Informatics subjects. This material requires computational thinking skills because it combines theory with programming code. Learning that only relies on PowerPoint presentations before practice makes the classroom atmosphere less interesting and tends to be boring. As a solution, an RPG genre educational game was developed as a learning medium for greedy algorithm material in grade XI Informatics. The development of this game uses the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The results of the analysis showed that there was no game-based learning media for this material, so the development was carried out as a learning innovation. The game that was developed received a very feasible assessment by media experts 93% of lecturers and 96% of teachers and material experts 99% of teachers and 93% of lecturers. Trials on individual, small, and large groups showed feasibility levels of 96%, 93%, and 95%, respectively. Based on these results, it can be concluded that this educational game is very good to be used as a learning medium for greedy algorithm material at the high school level.